The Owl and the QuestionsMatters of Philosophy - Markiewicz, Barbara Anna (Sensus Historiae, 2022)
To this day, the owl has beenis the most recognizable symbol of philosophy, its logo. By reference to the owl, two matters quite important for philosophy have been specified:, namely, first, the question of wisdom and, secondly, the question of the the peculiar character of philosophical knowledge. The first of them is historical and iconographic. The owl as a symbol of wisdom derives, like philosophy itself, from ancient Greece, and owes its importance mainly to the connection with the goddess Athena. It must be admitted, however, that philosophers were not particularlyvery interested in Athena’s relationship with wisdom (philosophy) and the owl, as well as inthe owls themselves. Among philosophers, only Hegel evokes the owl in the context of the classical owl-goddess-philosophy triad at the end of the “Preface” to The Principles of the Philosophy of Law. According to the majority of the interpreters ofinterpreting this passage, the owl was identified by Hegel with philosophical cognition. And this is the second matter important to the philosophy, in which owls have been involved.